LEGAL REGULATION OF INFORMATION ON INTERNET RESOURCES IN THE REPUBLIC OF KAZAKHSTAN (Journal of actual problems of jurisprudence, 2024)
This article delves into the legal framework governing information on internet resources within the Republic of Kazakhstan. In contemporary times, both information and its legal regulation possess unique characteristics, particularly evident in the context of the internet. The intricate interplay between global phenomena and the internet amplifies the notion of global governance. Within this expansive system, the self-regulation of information on internet resources necessitates legal oversight.Kazakhstan serves as a case study illustrating the internet's pivotal role as the primary and immediate source of information, facilitating interaction among numerous users. This prominence stems from the distinct characteristics of the internet when compared to traditional modes of information dissemination. A current issue in this field is conducting comprehensive research on the legal aspects of regulating information on internet resources. The goal of this study is to formulate recommendations for enhancing the legal framework governing the development of the Internet in Kazakhstan. This will be achieved through an in-depth, systematic analysis of the legal regulation of information on internet resources. The scientific novelty lies in the comprehensive examination of the legal regulation of information on internet resources in Kazakhstan, their systematization, and corresponding differentiation. The scientific significance of the work lies in the possibility of using the conclusions drawn for deeper theoretical research. The practical importance of this work is the potential application of its provisions to improve the existing legislation Kazakhstan  and law enforcement.Keywords: legal regulation, information, internet, legislation, information and communication technology